PUISI “ANGIN MAGRIB PASAR KEMBANG” KARYA SYAIFUDDIN GANI: TINJAUAN SEMIOTIK JONATHAN CULLERS - NFN Uniawati (Balai Bahasa Sulawesi Tengah, 2016)
The poem “Angin Magrib Pasar Kembang” written by Syaifuddin Gani has high religiosity. This poem gives akind of contemplation regarding the earth that is far from being essential. Therefore, this paper aims to revealthe inherent religiosity by using a qualitative method. The theory applied based of Jonathan Cullers thought.The analysis showed that this poem contains many metaphors about the journey of human life that is full withvarious temptations and punishments. The trip is essentially leading to a single point namely death. Death is the end of mortal life as the beginning of the immortal life.